Peningkatan Akurasi dan Presisi Analisa Spasial Pemodelan Banjir Kota Semarang Menggunakan Kombinasi Sistem Informasi Geografis Dan Metode Logika Fuzzy - Nugraha, Arief Laila (Diponegoro University, 2018)
One of the efforts to prevent and reduce the impact of the flood disaster is by the availability of information packaged into a digital map of the flood-prone areas, which can be used for planning control or early countermeasures. Geographic Information System (GIS) is an appropriate method in mapping flood-prone areas for large area coverage with a relatively short time. By integrating GIS technology and precise mathematical methods, it can produce spatial analysis with good precision and accuracy. Various methods to get the value of weighting and classification one of them by doing the method of decision making using Fuzzy Logic method. With the use of Fuzzy Logic method can strengthen the hypothesis that will be achieved in mapping the identification of disaster threats in a region in this case the flood Hazard of Semarang City. Fuzzy Logic and GIS method gives more valid result than using disaster catalog method with validity value equal to 54,84% from 31 field validation point with spread of flood threat in high class dominated in Genuk subdistrict.Â